Fighting non-communicable diseases in East Africa: assessing progress and identifying the next steps - Per Kallestrup; Joseph Mucumbitsi; Christian Kraef; Kaushik Ramaiya; Pamela A Juma; Francois Ndikumwenayo; Gerald Yonga (BMJ Global Health)
Sub-Saharan Africa has seen a rapid increase in non-communicable disease (NCD) burden over the last decades. The East African Community (EAC) comprises Burundi, Rwanda, Kenya, Tanzania, South Sudan and Uganda, with a population of 177 million. In those countries, 40% of deaths in 2015 were attributable to NCDs. We review the status of the NCD response in the countries of the EAC based on the available monitoring tools, the WHO NCD progress monitors in 2017 and 2020 and the East African NCD Alliance benchmark survey in 2017. In the EAC, modest progress in governance, prevention of risk factors, monitoring, surveillance and evaluation of health systems can be observed. Many policies exist on paper, implementation and healthcare are weak and there are large regional and subnational differences. Enhanced efforts by regional and national policy-makers, non-governmental organisations and other stakeholders are needed to ensure future NCD policies and implementation improvements.